2021
DOI: 10.1007/s40615-021-01179-1
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Falls Among Older Adults: a Systematic Review and Meta-analysis

Abstract: The aim of this systematic review and meta-analysis was to determine whether differences in reported fall rates exist between different ethnic groups. Searches were carried out on four databases: Medline, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Scopus, and Web of Science. Only English language studies with community-dwelling participants aged 60 + years were included. Studies also needed to compare fall prevalence for at least two or more ethnic groups. Two reviewers independently sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 52 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…We identified clinically relevant predictors of falls from the literature and through expert clinical opinion. 2 7 8 9 23 These included 30 predictors (44 predictor variables), covering patient demographics (age, sex, ethnicity, area based socioeconomic deprivation (index of multiple deprivation), body mass index (BMI), systolic and diastolic blood pressure), clinical characteristics (total cholesterol level, smoking status, alcohol intake), comorbidities (previous falls, memory problems, mobility issues, history of stroke, multiple sclerosis, activity limitation, syncope, cataract), and prescribed drugs (antihypertensives, opioids, hypnotics or benzodiazepines, antidepressants, anticholinergics) (see table S4.2 in the supplementary material). A recent literature review of falls clinical prediction tools by the National Institute for Health and Care Excellence identified the need for frailty to be considered as a predictor in models for use in the community.…”
Section: Methodsmentioning
confidence: 99%
“…We identified clinically relevant predictors of falls from the literature and through expert clinical opinion. 2 7 8 9 23 These included 30 predictors (44 predictor variables), covering patient demographics (age, sex, ethnicity, area based socioeconomic deprivation (index of multiple deprivation), body mass index (BMI), systolic and diastolic blood pressure), clinical characteristics (total cholesterol level, smoking status, alcohol intake), comorbidities (previous falls, memory problems, mobility issues, history of stroke, multiple sclerosis, activity limitation, syncope, cataract), and prescribed drugs (antihypertensives, opioids, hypnotics or benzodiazepines, antidepressants, anticholinergics) (see table S4.2 in the supplementary material). A recent literature review of falls clinical prediction tools by the National Institute for Health and Care Excellence identified the need for frailty to be considered as a predictor in models for use in the community.…”
Section: Methodsmentioning
confidence: 99%
“…Racial differences may also contribute to differences in fall prevalence. In a previous study, older Asian adults were reported to be less likely to fall than older adults in other ethnic groups (Wehner-Hewson et al, 2022). Similar to the findings in this study, the prevalence of multiple falls was found to be 6.7% among Chinese older adults in another study, with multiple falls further found to be associated with physical frailty ( OR = 6.79; Ma et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Falls are common among older people, with approximately 14%-30% of people living in communities experiencing falls. 1,2 Moreover, approximately half of those who experience falls experience more than one fall. 3 Falls in older adults can cause injuries such as fractures, dislocations, cuts, and bruises.…”
Section: Introductionmentioning
confidence: 99%